In vitro culture introduction of Silene genus of Caryophyllaceae family endemic species (Experimental biology, 2015)
Micropropagation and rooting protocols for 6 endemic species of Silene genus species were developed. Chemical andmechanical stratification and cold and warm stratification methods were used. Germination period of various specieshighly varied and temperature change was required for germination besides long term cultivation. Optimal media foreach species cultivation were selected. Impact of various hormones addition to MS medium on rhizogenesis inductionwas studied and media for plantlet rooting were selected. The optimal medium for rooting of 4 endemics – S. fetissovii,S. obovata, S. sussamyrica and S. ladyginae was MS medium with addition IAA (1mg/l). S. obovata normal plantletswith good root system were formed both on MS medium and with addition of 1 mg/l IAA. For S. schischkinii theoptimal medium for micropropagation was MS medium with addition of BAP (0.1 mg/l) and GA (0.2 mg/l). The mostsuitable medium for micropropagation and rooting S. eviscosa was MS medium with addition kinetin (0.1 mg/l) andGA (0.2 mg/l). MS medium was optimal medium for rooting of all species with addition IAA (1 mg/l).
Keywords: endemic; seed bank; micropropagation; germination; growth media; rooting of microcutting.